PEDAGOGICAL CONDITIONS FOR THE INTRODUCTION OF INNOVATIVE FORMS AND METHODS OF EDUCATION IN PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS (Universal International Scientific Journal, 2026)
This article discusses the forms and methods of effective implementation of STEAM (Science, Technology, Engineering, Arts, Mathematics) education in pedagogical higher education institutions from a scientific, theoretical and practical perspective. In the modern education system, it is important to prepare students to solve real-life problems, develop their competencies such as creative and critical thinking, technological and scientific literacy. Effective experiences of using interdisciplinary integration, project-based learning, design thinking, cooperative cooperation, interactive laboratories and gamification elements in the educational process through the STEAM approach are analyzed. The conclusions and recommendations indicate the prospects for the development of STEAM methodology for the higher education system of Uzbekistan.
Keywords: technology, STEAM education, innovative pedagogy, critical thinking, creativity, project-based learning, interactive labs, pedagogical methodology, cooperative learning.